DIVERSIFIKASI OLAHAN BERBASIS IKAN PATIN DI DESA JINGAH HABANG HILIR KECAMATAN KARANG INTAN KABUPATEN BANJAR KALIMANTAN SELATAN - Purnomo Purnomo; Juhana Suhanda (Faculty of Fisheries and Marine Resources of Lambung Mangkurat University-South Kalimantan, 2014)
Instead of processing technologies in order to fish based processed products diversification catfish in Banjar Regency is still urgently needed to introduce on the processors and consumers about the kinds of products processed fast-food restaurant. Diversification of processed fish catfish can increase the added value and the economy while increasing the Community fishery in the village of Jingah Habang Hilir with chilliesdownstream. Such understanding can serve as an alternative in action processing and preserving fish quality semi modern catfish in sufficient protein needs at the time of paceklik fishes. Skill enhancement programs through outreach, training and coaching forthe community must be in accordance with tha needs and characteristics of the community itself as businessmen is not an easy thing. Target audience itself as a partneris already accustomed to utilizing fish catfish processed products with variations, but it turns out the evaluation results in dire need of citations, formatations/models and practicaldirections for mking products such as ready made meatballs, nuggets and fish-baseddragon foot catfish to the development potential of aquatic resources optimally.